Valued waste/wasted value: Waste, value and the labour process in electronic waste recycling in Singapore and Malaysia. Issue 4 (24th February 2022) - Wong, Aidan M.
Abstract: This paper focuses on value creation in electronic waste, and supports the argument (c.f. Herod et al.,  2014) that 'waste' embodies congealed labour – the product of the labour process. This analysis of itinerant rag‐and‐bone collectors demonstrates that value creation by informal labour accrues as congealed labour in recycled e‐waste through the agentic acts of collecting, salvaging and extracting. This paper highlights the central role of informal labour in this labour process and pushes further the conceptualisation of 'wasted labour' (McGrath‐Champ et al.,  2015) by calling for greater attention to the agentic nature of labour in value creation, rather than simply being a passive means of production. Drawing on Marx's circuit of capital, this paper articulates the central role played by informal labour – an oft overlooked economic actor – in enabling the subsequent recycling processes and conceptualises them as pivotal to the recycling industry.